The Past, Present, and Future of Immune Repertoire Biology – The Rise of Next-Generation Repertoire Analysis - Six, Adrien; Mariotti-Ferrandiz, Encarnita; Chaara, Wahiba; Magadan, Susana; Pham, Hang-Phuong; Lefranc, Marie-Paule; Mora, Thierry; Thomas-Vaslin, Véronique; Walczak, Aleksandra M.; Boudinot, Pierre (Frontiers in Immunology, 2013)
T and B cell repertoires are collections of lymphocytes, each characterised by its antigen-specific receptor. We review here classical technologies and analysis strategies developed to assess Immunoglobulin (IG) and T cell receptor (TR) repertoire diversity, and describe recent advances in the field. First, we describe the broad range of available methodological tools developed in the past decades, each of which answering different questions and showing complementarity for progressive identification of the level of repertoire alterations: global overview of the diversity by flow cytometry, IG repertoire descriptions at the protein level for the identification of IG reactivities, IG/TR CDR3 spectratyping strategies, and related molecular quantification or dynamics of T/B cell differentiation. Additionally, we introduce the recent technological advances in molecular biology tools allowing deeper analysis of IG/TR diversity by next-generation sequencing (NGS), offering systematic and comprehensive sequencing of IG/TR transcripts in a short amount of time. NGS provides several angles of analysis such as clonotype frequency, CDR3 diversity, CDR3 sequence analysis, V allele identification with a quantitative dimension, therefore requiring high-throughput analysis tools development. In this line, we discuss the recent efforts made for nomenclature standardisation and ontology development. We then present the variety of available statistical analysis and modelling approaches developed with regards to the various levels of diversity analysis, and reveal the increasing sophistication of modelling approaches. To conclude, we provide some examples of recent mathematical modelling strategies and perspectives that illustrate the active rise of a “next-generation” of repertoire analysis.